STRATEGI KINERJA KARYAWAN DALAM MENINGKATKAN PRODUKTIFITAS PADA BUMDES DI KECAMATAN BANTAN - Ahmad Tarmizi; Irawan Irawan; Hadi Wijaya (CV. KAMPUSA AKADEMIK PUBLISHING, 2025)
This study aims to analyze the employee performance strategies implemented by BUMDes in Bantan District and their impact on employee productivity. The research uses a descriptive quantitative approach with simple linear regression analysis to examine the relationship between performance strategies and employee productivity. Data were collected through a questionnaire distributed to 50 randomly selected employees of BUMDes. The results show a significant positive relationship between the implementation of performance strategies and employee productivity, with an R-squared value of 65.8%. This indicates that improving the quality of performance strategies, such as training, rewards, and effective human resource management, can enhance employee productivity. This study provides recommendations for BUMDes to strengthen training programs and incentives for employees as part of efforts to increase productivity.